The anticaries effects of pit and fissure sealant in the first permanent molars of school-age children from Guangzhou: a population-based cohort study - Weijia Liu; Lihua Xiong; Jianbo Li; Chongshan Guo; Weihua Fan; Shaohong Huang (BMC, 2019)
Abstract Background Analyses of the effects of pit and fissure sealant have been based on small samples and lack large-scale field evaluation data in China. The aim of this study was to understand the effect of pit and fissure sealant in preventing caries in the first permanent molars (FPMs) of children in Guangzhou. Methods We conducted a population-based cohort study using the database of the pit and fissure sealant program of Guangzhou. The carious status and sealant retention of the FPMs were assessed in 4,822 school children who received pit and fissure sealant 3 years prior to the study. The control group included 4,396 children who had indications for receiving pit and fissure sealant but were not treated and were matched according to sex, age and school. Results In the sealant group, the rate of sealant retention in the FPMs was 72.2%. Children in the sealant group had a 37% decreased risk of dental caries compared with the control group (adjusted HR = 0.63 [95% confidence interval (CI), 0.57-0.69], P < 0.001). Compared to no sealant use, the use of pit and fissure sealants reduced the risk of developing dental caries by 44% after 3 years in the FPMs of children from rural areas, reflecting a greater reduction than that among urban children (35%) during the same period (urban: adjusted hazard ratio (HR) = 0.65 [95% CI, 0.58-0.72]; rural: adjusted HR = 0.56 [95% CI, 0.45-0.70], P < 0.001). The mean number of decayed, missing, or filled permanent teeth (DMFT) in the control group was higher than that in the sealant group, and the difference was statistically significant regardless of sex. Conclusions Pit and fissure sealant has a significant preventive effect against dental caries in the FPMs, especially for children in rural areas; thus, this sealant represents an effective technique for preventing and controlling dental caries.